An unusual case of ectrodactyly in a free-living European hedgehog (Erinaceus europaeus, Linnaeus 1758) - Garcês, Andreia; Pires, Isabel; Sargo, Roberto; Silva, Filipe (Journal of Advanced Veterinary Research, 2024)
This report aimed to present a case of ectrodactyly in a free-living adult female Erinaceus europaeus. At radiography and post-mortem dissection, the right hind limb developed 2 digits and aplasia of 3 digits. No other abnormality was found in this case. Various teratogens may be responsible for occurring skeletal anomalies. To the best of our knowledge, the present study is the first report of ectrodactyly in this species.